Management of environmentally friendly fishing gears based on the code of conduct for responsible fisheries in Pidie District. Issue 1 (February 2021) - Chaliluddin, M A; Rahmah, A; Aprilla, R M; Rizwan, T; Ikram, M; Satria, D; Yani, F I
Abstract: Fishery management is all efforts that are integrated in laws and regulations in the field of fisheries to achieve sustainable productivity of aquatic biological resources. Fishery management activities in a water area with a high number productivity of fish resources have to pay attention to aspects that can support of goal the achievement of environmentally friendly and sustainable fisheries management. Pidie District is located in the east of Aceh which is directly opposite the Malacca Strait and has a high productivity of fish resources using various fishing gear. The purpose of this study was to determine the management strategy for environmentally friendly fishing gear based on the code of conduct for responsible fisheries (CCRF) in Pidie District. The data analysis method used in this research is descriptive, scoring, and SWOT analysis. The results, strategies used within environmentally friendly capture fisheries management are enhancement, monitoring, and law enforcement upon the un - selective fishing gears that tend to be destructive, optimize human resources in utilizing fish resources to environmentally friendly capture fisheries management in both of pre-production to post – production, improve the capacity of facilities and infrastructure in supporting environmentally friendly capture fisheries operations, monitor fisheries activities as well surrounding areas of port upon the pollution that harms environmental quality order, and socialization upon the used of environmentally friendly current technologies.